Health for Some
XVIII, 278 p.
Keywords: Poverty and inequality are among the most significant determinants of health. Increased inequality gaps associated with globalization have serious implications for global health. Global changes in political economy shape global health influencing who bears the burden from epidemics, unhealthy environments and lack of access to health care.